2004
DOI: 10.1080/10739680490266207
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Glucocorticoid and Mineralocorticoid Receptor Density in the Microcirculation of the Spontaneously Hypertensive Rat

Abstract: These results suggest that the enhanced sensitivity of the SHR to glucocorticoids and aldosterone may be in part associated with enhanced glucocorticoid and mineralocorticoid receptor densities in the microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…25 What mechanism may raise the count of circulating leukocytes with pseudopods in the SHR? Although there is no significant difference in circulating levels of corticosteroids between WKY and SHR, 26 glucocorticoid receptors have higher density 27 and sensitivity in SHR than WKY, 28 suggesting that the abnormal response to glucocorticoids is a requirement for sustained elevation of blood pressure in SHR. Fluid shear stress serves to inactivate leukocytes by downregulation of membrane CD18 molecules 29 and retraction of pseudopods.…”
Section: Discussionmentioning
confidence: 98%
“…25 What mechanism may raise the count of circulating leukocytes with pseudopods in the SHR? Although there is no significant difference in circulating levels of corticosteroids between WKY and SHR, 26 glucocorticoid receptors have higher density 27 and sensitivity in SHR than WKY, 28 suggesting that the abnormal response to glucocorticoids is a requirement for sustained elevation of blood pressure in SHR. Fluid shear stress serves to inactivate leukocytes by downregulation of membrane CD18 molecules 29 and retraction of pseudopods.…”
Section: Discussionmentioning
confidence: 98%
“…In microvessels, both the GC and the mineralocorticoid receptors are expressed in all layers, and their abundances are greater in spontaneously hypertensive rats than in normotensive controls. 40 Undernutrition could reduce expression of placental 11b-HSD-2 and thereby increase transfer of active GC into the fetal compartment, which in turn could directly bind to vascular GC receptors and inhibit VEGF and VEGF receptor expression and ultimately angiogenesis. Correspondingly, numerous studies have demonstrated an inhibitory effect of GC on VEGF abundance and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both endothelial and VSMC MR are involved in BP (in basal conditions and in response to AngII infusion) [11,15,19] in the absence of alteration of renal Na + homeostasis, pointing on a specific role of MR expressed in the vasculature. Indeed, MR expression can be increased in vessels in some pathological situations such as hypertension [5].…”
Section: Discussionmentioning
confidence: 99%